Evaluation of knowledge transfer for occupational safety and health in an organizational context: development of an evaluation framework. Issue 1 (2nd January 2016) - Crawford, Joanne O.; Davis, Alice; Walker, Guy; Cowie, Hilary; Ritchie, Peter
Abstract: The roots of knowledge transfer (KT) can be traced back to the 1960s and the development of conceptual frameworks to improve the use of research from theory into practice. Its relevance to occupational safety and health (OSH) is clear in that often practitioners are aiming to transfer knowledge to employees to reduce health or safety risks in the working environment. This paper examines methodologies and tools that can be used for KT in the organizational context and identified those that were most relevant in OSH. The methodology development process is described within the paper which used the Diffusion of Innovations theory as a framework to describe the type of knowledge being transferred, the persuasion route used, the decision of whether new knowledge was adopted, how the KT was implemented and how success or failure of an intervention could be assessed. Using this framework structured interviews and shorter employee surveys were developed to evaluate KT in an organizational setting after an OSH intervention. In addition, further questions were developed using KT tools to describe the properties of the knowledge transferred, the level of media richness and its appropriateness in a given context and examination of the methods used within a sender receiver framework. The methodology development process allowed the production of a question set to enable the research team to interview and survey stakeholders involved in OSH interventions in the workplace.